Representation of occupational information across resources and validation of the occupational data for health model - Rajamani, Sripriya (J Am Med Inform Assoc, 2017)
Reports by the National Academy of Medicine and leading public health organizations advocate including occupational information as part of an individual’s social context. Given recent National Academy of Medicine recommendations on occupation-related data in the electronic health record, there is a critical need for improved representation. The National Institute for Occupational Safety and Health has developed an Occupational Data for Health (ODH) model, currently in draft format. This study aimed to validate the ODH model by mapping occupation-related elements from resources representing recommendations, standards, public health reports and surveys, and research measures, along with preliminary evaluation of associated value sets. All 247 occupation-related items across 20 resources mapped to the ODH model. Recommended value sets had high variability across the evaluated resources. This study demonstrates the ODH model’s value, the multifaceted nature of occupation information, and the critical need for occupation value sets to support clinical care, population health, and research.